Association Between Plasma Apolipoprotein M With Alzheimer’s Disease: A Cross-Sectional Pilot Study From China - Xin, Jia-Yan; Huang, Xiao; Sun, Ying; Jiang, Hai-Song; Fan, Jin; Yu, Neng-wei; Guo, Fu-Qiang; Ye, Fang; Xiao, Jun; Le, Wei-dong; Yang, Shao-Jie; Xiang, Yang (Frontiers in Aging Neuroscience, 2022)
Background: Recent evidence of genetics and metabonomics indicated a potential role of apolipoprotein M (ApoM) in the pathogenesis of Alzheimer’s disease (AD). Here, we aimed to investigate the association between plasma ApoM with AD. Methods: A multi-center, cross-sectional study recruited AD patients (n=67), age- and sex-matched cognitive normal (CN) controls (n=73). We examined and compared the plasma levels of ApoM, tau phosphorylated at threonine 217 (p-tau217) and neurofilament light (NfL). Multivariate logistic regression analysis was applied to determine the association of plasma ApoM with the presence of AD. The correlation analysis was used to explore the correlations between plasma ApoM with cognitive function [mini-mental state examination (MMSE) and Montreal cognitive assessment (MoCA)], activities of daily living (ADL), and the representative blood-based biomarkers. Receiver operating characteristic (ROC) analysis and Delong’s test were used to determine the diagnostic power of plasma ApoM. Results: Plasma ApoM and its-derived indicators (ratios of ApoM/TC, ApoM/TG, ApoM/HDL-C and ApoM/LDL-C) were significantly higher in AD group than CN group (each p < 0.0001). After adjusted for the risk factors of AD, the plasma ApoM and its-derived indicators were significantly associated with presence of AD, respectively. ApoM (OR=1.058, 95%CI: 1.027-1.090, p < 0.0001), ratios of ApoM/TC (OR=1.239, 95%CI: 1.120 -1.372, p < 0.0001), ApoM/TG (OR=1.064, 95%CI: 1.035 -1.095, p < 0.0001), ApoM/HDL-C (OR=1.069, 95%CI: 1.037-1.102, p < 0.0001) and ApoM/LDL-C (OR=1.064, 95%CI:1.023-1.106, p = 0.002). In total participants, plasma ApoM and its-derived indicators were significantly positively correlated with plasma p-tau217, NfL and ADL (each p < 0.0001), and significantly negatively correlated with MMSE and MoCA (each p < 0.0001), respectively. In further subgroup analyses, these associations remained in different APOE 4 status participants and sex subgroups. ApoM/TC and ApoM/TG had a remarkably larger area under the curve (AUC) than ApoM (both p < 0.05), respectively. The independent addition of ApoM and its-derived indicators to basic model led to a significant improvement of diagnostic power (each p < 0.05). Conclusions All the findings preliminarily uncovered the association between plasma ApoM and AD, and provided more evidence of the potential of ApoM as a candidate biomarker of AD.